Density Functional Theoretical Analysis of the Molecular Structural Effects on Raman Spectra of β-Carotene and Lycopene - 刘伟龙 王志刚 郑植仁 蒋礼林 杨延强 赵连城 苏文辉 (Chinese journal of chemistry, 2012)
The molecular structural and Raman spectroscopic characteristics of fl-carotene and lycopene are investigated by density functional calculations. The effects of molecular structure and solvent environment on the Raman spectra are analyzed by comparing the calculated and measured results. It is found that the B3LYP/6-31G（d） method can predict the reasonable result for β-carotene, but the vl Raman activities of lycopene overflow at all the used theo- retical methods because of the longer conjugation length in β-carotene impedes the delocalization of ~r-electrons The calculated results indicate that the rotation of β-rings shortens the effective conjugation length, and results in higher frequency and lower activity of the vl mode in /q-carotene than lycopene. The measured vl bands of β-carotene and lycopene shift respectively to higher and lower frequencies in solution compared with that in crystals since the crystal packing forces can lead to different conformational variations in the carotenoids molecules. The polarized continuum model theoretical analysis suggests that solvent has slight （significant） effects on the Raman frequencies （intensities） of both carotenoids.